Urinary and dietary sodium and potassium associated with blood pressure control in treated hypertensive kidney transplant recipients: an observational study - Saint-Remy Annie (BMC Nephrology, 2012)
Abstract Background In kidney transplant (Kt) recipients , hypertension is a major risk for cardiovascular complications but also for graft failure. Blood pressure (BP) control is therefore mandatory. Office BP (OBP) remains frequently used for clinical decisions, however home BP (HBP) have brought a significant improvement in the BP control. Sodium is a modifiable risk factor, many studies accounted for a decrease of BP with a sodium restricted diet. Increased potassium intake has been also recommended in hypertension management. Using an agreement between office and home BP, the present study investigated the relations between the BP control in Kt recipients and their urinary excretion and dietary consumption of sodium and potassium. Methods The BP control defined by OBP <140/90 mmHg and HBP <135/85 mmHg was tested in 70 Kt recipients (mean age 56 ± 11.5 years; mean graft survival 7 ± 6.6 years) treated with antihypertensive medications. OBP and HBP were measured with a validated oscillometric device (Omron M6®). The 24-hour urinary sodium (Na+) and potassium (K+) excretions as well as dietary intakes were compared between controlled and uncontrolled (in office and at home) recipients. Non parametric Wilcoxon Mann–Whitney Test was used for between groups comparisons and Fisher's exact test for frequencies comparisons. Pearson correlation coefficients and paired t-test were used when sample size was >30. Results Using an agreement between OBP and HBP, we identified controlled (21%) and uncontrolled recipients (49%). Major confounding effects susceptible to interfere with the BP regulation did not differ between groups, the amounts of sodium excretion were similar (154 ± 93 vs 162 ± 88 mmol/24 h) but uncontrolled patients excreted less potassium (68 ± 14 vs 54 ± 20 mmol/24 h; P = 0.029) and had significantly lower potassium intakes (3279 ± 753 vs 2208 ± 720 mg/24 h; P = 0.009), associated with a higher urinary Na+/K + ratio. Systolic HBP was inversely and significantly correlated to urinary potassium (r = −0.48; P = 0.002), a positive but non significant relation was observed with urinary sodium (r = 0,30;P = 0.074). Conclusions Half of the treated hypertensive Kt recipients remained uncontrolled in office and at home. Restoring a well-balanced sodium/potassium ratio intakes could be a non pharmacological opportunity to improve blood pressure control.